We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
145
1
avatar

A ( 0,-1)

 

B (0,5)

 

C (-2,3)

 

D (-2,-1)

 Mar 7, 2019
 #1
avatar+105347 
+1

y = x + 5

y = -2x -1

 

Set the y's equal

 

x + 5 =  -2x - 1      add2x to both sides, subtract 5 from both sides

 

3x = - 6     divide both sides by   3  

 

x = -2

 

And using  y = x + 5 to find y, we have

 

y = (-2) + 5

 

y = 3

 

cool cool cool

 Mar 7, 2019
edited by CPhill  Mar 7, 2019

16 Online Users

avatar
avatar